A theory of transition in sports career - Válková, H. (Studia Sportiva, 2017)
The article is oriented on explanation of the theoretical framework of the transition theory. The origin of this theory, terminology development and approaches how to adapt to it in practice are presented. Three basic approaches are developed in research and practice: a) a drop-out phenomenon between stages, b) a stage of involution and dual career, c) a long-term talent development. The acceptance of biodromal and holistic approach are stressed which means that the principles of sports training should be accompanied with the perception of importance of a social environment (parents, coaches, peers, sports club policy). A classic model of the theory consists of four developmental stages with typical markers in each stage (from early childhood up to the period of involution). The theory can be applied in both recreational participation in one`s daily life-span development, and in the sports talent development and professional sports career including the stage of involution.